IMPLEMENTATION OF EXPERT SYSTEMS IN MAPPING THE LEARNING STYLES OF HIGH SCHOOL STUDENTS - Dermawan, Gugun; Saputra, Hendra Nelva; Razilu, Zila (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This study aims to map the learning styles of students at SMA Negeri 2 Lasalimu Selatan using an expert system. The method used in this research is a quantitative approach, with data collected through a learning style questionnaire filled out by the students. The sample consists of 160 students from grades X and XI, with data analysis using percentage formulas to analyze the distribution of learning styles based on grade level, classroom, and age. The results show that in grade X, the visual learning style dominates (42%), while in grade XI, the auditory learning style is more dominant (45%). The kinesthetic learning style remains at a low percentage in both grades. Based on these results, it is recommended that teachers design learning approaches that accommodate visual and auditory learning styles, while also paying attention to students with kinesthetic learning styles, even though their percentage is low. More personalized learning based on students' learning styles is expected to improve the effectiveness of the learning process and students' academic achievements. ABSTRAKPenelitian ini bertujuan untuk memetakan gaya belajar siswa SMA Negeri 2 Lasalimu Selatan menggunakan sistem pakar. Metode yang digunakan dalam penelitian ini adalah pendekatan kuantitatif, dengan pengumpulan data melalui kuesioner gaya belajar yang diisi oleh siswa. Sampel penelitian berjumlah 160 siswa dari kelas X dan XI, dengan analisis data menggunakan rumus persentase untuk menganalisis distribusi gaya belajar berdasarkan jenjang kelas, kelas, dan usia. Hasil penelitian menunjukkan bahwa pada kelas X, gaya belajar visual mendominasi (42%), sedangkan pada kelas XI, gaya belajar auditori lebih dominan (45%). Gaya belajar kinestetik masih berada pada persentase yang rendah pada kedua kelas tersebut. Berdasarkan hasil penelitian tersebut, disarankan kepada guru untuk merancang pendekatan pembelajaran yang mengakomodasi gaya belajar visual dan auditori, dengan tetap memperhatikan siswa dengan gaya belajar kinestetik, meskipun persentasenya rendah. Pembelajaran yang lebih personal berdasarkan gaya belajar siswa diharapkan dapat meningkatkan efektivitas proses pembelajaran dan prestasi akademik siswa.